CALCULATION SYSTEM COMPUTERIZED ROYALTY / FEE AUTHOR IN CV. GHALIAN INDONESIA - Irwan Irwan; Sahni D., Ir. Sahni D., Ir. (Jurnal Sistem Informasi, 1998)
Once the importance of the role of presenting the report royalties /  fee author on the CV. Ghalia Indonesia, especially for the administration / administration because it can affect perpormance and improvement of the company. Activities of this author's presentation of the report i s still using the manual way, ie in terms of the counting process by the administrative fee, in addition, it needs a lot of places to store the lists of books and lists the security of transactions take a long time and other things. Seeing the lack of efficiency of the above activities, the problem also influences the effectiveness of future work, while the number of lists of books, branches and transactions continue to increase and require more rapid and precise information, it is worth noting and created a system computerize.